Iatrogenic botulism cases after gastric and axillary application of botulinum toxin and review of literature - Fatma Eser; İmran Hasanoğlu; Bircan Kayaaslan; Ayşe Kaya Kalem; Şule Bilen; Gürdal Orhan; Rahmet Güner (Journal of Infection in Developing Countries)
Introduction: Iatrogenic botulism is a rare, serious disease that progresses with descending paralysis and develops after cosmetic or therapeutic botulinum toxin-A (BoNT-A) application.